Gymnastics adapted to School- Program (Fiep Bulletin - online, 2015)
The necessity of physical activities in school is generally not contested. Besides the imperative character it assumes to-day, it is determined on one hand by the rhythm of modern life, on the other hand by the extention of sedentary life, due itself to constant technical progress.